La schizofrenia non è una malattia neurologica - Fiori Nastro, Paolo (Il sogno della farfalla, 2010)
The Author briefly presents M. Fagioli’s 1962 article, Chronic epileptic psychosis and pseudoschizophrenic syndrome, republished in this issue, highlighting the distance that separates its rigorously psychopathological formulation and its idea of a possible cure for mental illness from “neo-kraepelinian” developments of psychiatry of the last few decades that have given rise to the DSM.